2005
DOI: 10.1002/mc.20107
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting NAD(P)H:quinone oxidoreductase (NQO1) in pancreatic cancer

Abstract: NAD(P)H:quinone oxidoreductase (NQO1) functions as an important part of cellular antioxidant defense by detoxifying quinones, thus preventing the formation of reactive oxygen species (ROS). The aim of our study was to determine if NQO1 is elevated in pancreatic cancer specimens and pancreatic cancer cell lines and if so, would compounds previously demonstrated to redox cycle with NQO1 be effective in killing pancreatic cancer cells. Immunohistochemistry of resected pancreatic specimens demonstrated an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…NQO1 is an FAD-dependent direct two-electron reductase that can use either NADH or NADPH as reducing cofactor and reduces quinones directly to hydroquinones. Relatively high levels of NQO1 protein and activity have been detected in many human solid tumors, including lung, breast, colon, ovary, and pancreas (Schlager and Powis, 1990;Siegel and Ross, 2000;Lewis et al, 2005). We have demonstrated that NQO1 protein levels in both normal and tumor tissues are influenced by a single-nucleotide polymorphism in the NQO1 gene.…”
Section: Introductionmentioning
confidence: 72%
“…NQO1 is an FAD-dependent direct two-electron reductase that can use either NADH or NADPH as reducing cofactor and reduces quinones directly to hydroquinones. Relatively high levels of NQO1 protein and activity have been detected in many human solid tumors, including lung, breast, colon, ovary, and pancreas (Schlager and Powis, 1990;Siegel and Ross, 2000;Lewis et al, 2005). We have demonstrated that NQO1 protein levels in both normal and tumor tissues are influenced by a single-nucleotide polymorphism in the NQO1 gene.…”
Section: Introductionmentioning
confidence: 72%
“…Importantly, constitutive NQO1 overexpression leading to high specific enzymatic activity is associated with various human malignancies including non-small cell lung cancer, pancreas carcinoma, and breast and colon adenocarcinoma, and specific enzymatic activity can differ by up to 20 fold between malignant and unaffected surrounding tissue [42,51]. Recent research suggests that NQO1-overexpression in tumors may serve to accommodate the needs of rapidly metabolizing cells to regenerate NAD + from NADH, a metabolic adaptation of cancer cells that ensures high glycolytic flux independent of NAD + regeneration by mitochondrial respiration that is often compromised in cancer cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…A prototypical Nrf2 downstream protein, NQO1 (NAD(P)H:quinone oxidoreductase 1), was found to be over-expressed ten-fold compared to normal human pancreatic tissue (Logsdon et al, 2003). Strong immunohistochemical staining for NQO1 has also been demonstrated in premalignant pancreatic dysplastic lesions, known as Pancreatic Intraepithelial Neoplasias (PanINs), suggesting that it is frequently activated early in pancreatic carcinogenesis (Awadallah et al, 2008;Lewis et al, 2005). However, specificity for PDAC may be poor since NQO1 is also over-expressed in non-tumorous pancreatic specimens from smokers, and in pancreatitis tissue Lyn-Cook et al, 2006).…”
Section: Are-driven Gene Expression Is Increased In Pancreatic Cancermentioning
confidence: 99%